Sociodemographic characteristics of patients undergoing myocardial revascularization in a hospital in Fortaleza-Ce - Francisca Elisângela Teixeira Lima; Thelma Leite de Araújo; Thereza Maria Magalhães Moreira; Marcos Venícius de Oliveira Lopes; Albeniza Mesquita de Medeiros (Rev Rene)
The aim of this research was to describe the characteristics of patients undergoing myocardial revascularization. It was a descriptive study, developed in the clinic of a public hospital which is reference in cardiology in Fortaleza-CE. The population was composed by 146 patients undergoing myocardial revascularization during the period of data collection, in that institution. The sample consisted of 78 patients who met the criteria for inclusion. The results were grouped in tables and analyzed descriptively. The main socio demographic characteristics were: male (62, 8%), age > 60 years (68, 0%), low education (73, 1%), family income of up to one minimum wage (55, 1%), presence family history of ischemic heart diseases (65, 4%). The knowledge of such characteristics will allow the nurses, who look after the patients with cardiac diseases, to work with them, besides reinforcing the education strategies for health promotion adopted along with the populations with such features.